Fundamental insight in the design of multifilament MgB2 joint for boosting the persistent-mode operation. (1st November 2021) - Kim, Su-Hun; Patel, Dipak; Maeda, Minoru; Kim, Minhee; Lee, Se-Hee; Choi, Seyong; Kim, Jung Ho
Abstract: Persistent-mode operation is a key feature of magnetic resonance image systems to improve the required field stability. The superconducting joint is known to be beneficial for reducing all the resistant components in an electrically closed-circuit. The joint technique of magnesium diboride (MgB2 ) multifilamentary wire, however, is the main obstacle to the use of magnet in practical applications. In response, herein, we designed and developed a unique configuration of superconducting joint to further enhance the interconnection of exposed cores between two 18-multifilamentary wires. It was confirmed that developed joint samples achieved high critical current similar to a non-jointed wire. The proposed joint technique was directly applied to the MgB2 single-turn coil and MgB2 magnet for estimating a joint property through persistent-mode operation. This work provides fundamental insights into the design of persistent-mode MgB2 magnets to boost magnetic resonance image systems.